2005
DOI: 10.1002/jbt.20089
|View full text |Cite
|
Sign up to set email alerts
|

Modulation of sulfur mustard induced cell death in human epidermal keratinocytes using IL‐10 and TNF‐α

Abstract: We compared the effects of overexpressing a tightly regulated anti-inflammatory cytokine, interleukin 10 (IL-10), and the pro-inflammatory cytokine tumor necrosis factor-alpha (TNF-alpha) on sulfur mustard induced cytotoxicity in human epidermal keratinocytes. Both cytokines were overexpressed when compared with the cells transfected with the empty vector as determined by quantitative ELISA. Cells overexpressing interleukin 10 suppressed the pro-inflammatory cytokines interleukin 8 and interleukin 6 following … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
7
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 46 publications
(47 reference statements)
3
7
0
Order By: Relevance
“…Following SM exposure, previous studies have shown that normal human keratinocytes increase levels of IL1b, IL6, IL8 and TNFa in a dose dependent manner (Arroyo et al, 2000(Arroyo et al, , 2004 which is associated with epidermal cell death (Qabar et al, 2005;Ruff and Dillman, 2010). Our results showing a dose dependent increase of both mRNA for these inflammatory mediators and number of pyknotic nuclei in skin of hairless mice are concordant with these in vitro studies.…”
Section: Discussionsupporting
confidence: 95%
“…Following SM exposure, previous studies have shown that normal human keratinocytes increase levels of IL1b, IL6, IL8 and TNFa in a dose dependent manner (Arroyo et al, 2000(Arroyo et al, , 2004 which is associated with epidermal cell death (Qabar et al, 2005;Ruff and Dillman, 2010). Our results showing a dose dependent increase of both mRNA for these inflammatory mediators and number of pyknotic nuclei in skin of hairless mice are concordant with these in vitro studies.…”
Section: Discussionsupporting
confidence: 95%
“…Furthermore, a primary role for p38 in SM-induced cytokine production has now been demonstrated using two different approaches; RNAi and SB203580. These findings have important implications for future research given that NF-κB has long been implicated as playing a primary role in SM-induced inflammatory cytokine production [9,[12][13][14]. Similarly, p53 is widely believed to play a prodeath role in SMexposed cells [10,23,24,26,27].…”
Section: Discussionmentioning
confidence: 91%
“…Both p38 and NF-κB are activated in SM-exposed cells [7,[9][10][11], but it is NF-κB that has long been implicated as playing a primary role in SM-induced inflammatory cytokine production [9,[12][13][14]. These implications have been based on the observations that (1) SM-or SM analog-induced modulation of NF-κB activity in gel shift assays correlates with inflammatory or protection events, and (2) NF-κB exhibits proinflammatory activity in other systems [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting aspect of the involvement of TACE/ADAM17 in HD-induced pathogenesis may be its role in the release of the inflammatory cytokine TNF␣. Indeed, an increase in the production of inflammatory cytokines including TNF␣ by cells in response to exposure to HD has been reported (Arroyo et al, 2000(Arroyo et al, , 2004Wormser et al, 2005;Qabar et al, 2005). Thus, inhibition of TACE/ADAM17 might temper the inflammatory reaction that accompanies HD-induced tissue damage.…”
Section: Discussionmentioning
confidence: 92%